Plasticity analysis by synchrotron radiation in a Mg97Y2Zn1 alloy with bimodal grain structure and containing LPSO phase. (1st August 2015) - Garces, G.; Morris, D.G.; Muñoz-Morris, M.A.; Perez, P.; Tolnai, D.; Mendis, C.; Stark, A.; Lim, H.K.; Kim, S.; Shell, N.; Adeva, P.
Abstract: Deformation behaviour has been examined by synchrotron radiation diffraction in an extruded magnesium – long-period-stacking-order phase alloy comprising three components of microstructure. The variation of internal strains and intensities of the important crystallographic planes of the two phases has been examined during compression at several temperatures. The long-period-stacking-order phase remains elastic to stresses beyond the macroscopic yield stress while deformation in the magnesium matrix is dominated by twinning and basal slip, with the coarse-grained regions deforming plastically at stresses well below the macroscopic yield stress while regions with fine grain size deform plastically only at much higher stresses.